Why I am what I am - MacArthur, Robert Stuart, 1841-1923 (Peerless series ;, 1891)
Why I am a Baptist / R.S. MacArthur -- Why I am a Presbyterian / C.S. Robinson -- Why I am a Methodist Episcopalian / G.H. McGrew -- Why I am an Episcopalian / W.R. Huntington -- Why I am a Catholic / Walter Elliott -- Why I am a Congregationalist / Lyman Abbott -- Why I am a Universalist / C.H. Eaton -- Why I am a New Churchman / S.S. Seward -- Why I am a Unitarian / J.W. Chadwick -- Why I am a Jew / Gustav Gottheil -- Why I am a Lutheran / G.F. Krotel -- Why I am a Friend / J.J. Cornell -- Why I am a Disciple / B.B. Tyler -- Why I am a Seventh-Day Baptist / A.H. Lewis -- Crumbling creeds / R.G. Ingersoll.